ICSH guidelines for the verification and performance of automated cell counters for body fluids. (14th March 2014) - Bourner, G.; De la Salle, B.; George, T.; Tabe, Y.; Baum, H.; Culp, N.; Keng, T. B.; ,
Summary: One of the many challenges facing laboratories is the verification of their automated Complete Blood Count cell counters for the enumeration of body fluids. These analyzers offer improved accuracy, precision, and efficiency in performing the enumeration of cells compared with manual methods. A patterns of practice survey was distributed to laboratories that participate in proficiency testing in Ontario, Canada, the United States, the United Kingdom, and Japan to determine the number of laboratories that are testing body fluids on automated analyzers and the performance specifications that were performed. Based on the results of this questionnaire, an International Working Group for the Verification and Performance of Automated Cell Counters for Body Fluids was formed by the International Council for Standardization in Hematology (ICSH) to prepare a set of guidelines to help laboratories plan and execute the verification of their automated cell counters to provide accurate and reliable results for automated body fluid counts. These guidelines were discussed at the ICSH General Assemblies and reviewed by an international panel of experts to achieve further consensus.